Travel guide Tokyo, Nikko, Kamakura, Hakone, Yokohama (Tokyo, 1981)
To give you an idea of how to get about Tokyo and to help make the foreign visistor's stay more pleasant and fruitful, this compact guidebook is divided into 19 sections.